PRECONDITIONS OF PUBLIC BUILDINGS AND STRUCTURES FORMING ON THE TERRITORY OF KRYVYI RIH QUARRIES (Academic journal Industrial Machine Building Civil Engineering, 2017)
In that article the analysis of quarries of Kryvyi Rih area was conducted. Analysis was conducted on the following criteria: quarry area, structure, shape in plan, closed-open plan type, water cutting and location. Based on the analysis the sequence of construction and reclamation of disturbed areas were determined. There were allocated three stages of quarries reclamation and the civilian buildings in the quarries forming. It was found that for public buildings, formed in artificial terrain in the center of the city it is advisable to choose a commercially viable option. In the periphery it is advisable to have research centers, agro-technological parks. Within sanctuaries and nature reserves it is useful to locate museums of nature and information centers. In recreational areas it is advisable to place entertainment objects and hotels. It was established the influence of the quarry geometry, its location relative to the morphological structures, isolation, produced raw materials, composition of the soil to the form of the buildings and structure formed in the quarry. Features of the quarry structure dictate also features of engineering territory preparation.